Changing Africa - Rob Bowden (Hong Kong Heinemann Raintree Books, 2010)
What is the population of Africa today? How do Fair Trade organizations help Africa? Which African country pioneered the world's largest engineering project? Africa Focus offers fascinating and detailed coverage of a diverse and complex continent. The four titles examine different aspects of Africa and its interaction with the world.
Keywords: People And Places -- People And Places; Places Of The World -- Places Of The World